The effectiveness of a construction worksite prevention program on work ability, health, and sick leave: results from a cluster randomized controlled trial - Karen M Oude Hengel; Birgitte M Blatter; Henk F van der Molen; Paulien M Bongers; Allard J van der Beek (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: This study aimed to investigate the effectiveness of a prevention program on work ability, health, and sick leave targeted at construction worksites. METHODS: A total of 15 departments (N=297 workers) from 6 construction companies participated in this cluster randomized controlled trial and were randomly allocated to the intervention (8 departments; N=171 workers) or control (7 departments; N=122 workers) group. The intervention consisted of two individual training sessions with a physical therapist aimed at lowering the physical workload, a rest-break tool to improve the balance between work and recovery, and two empowerment training sessions to increase the worker's influence at the worksite. Data on work ability, physical and mental health status, and musculoskeletal symptoms were collected at baseline, and at 3, 6, and 12 months follow-up. Sick leave data were obtained from the companies. RESULTS: Overall, no differences in work ability [β 0.02, 95% confidence interval (95% CI) -0.34-0.37] or physical and mental health status (β -0.04, 95% CI -1.43-1.35, and β 0.80 95% CI -0.51-2.11, respectively) were found between the intervention and control group. The intervention showed an overall decline in musculoskeletal symptoms (ranging from OR 0.68, 95% CI 0.34-1.33, to OR 0.86, 95% CI 0.47-1.57) and long-term sick leave (OR 0.44, 95% CI 0.13-1.26) among construction workers. Both reductions were not statistically significant. CONCLUSION: The prevention program seemed to result in a beneficial but not statistically significant decline in the prevalence of musculoskeletal symptoms and long-term sick leave among construction workers, but showed no effects with regard to work ability, physical health, and mental health.